(3QSGdI aj hba MeRI hgTGes - (3eMeO Hf CMeO Hf HVMGf Hf Yjf GdOhdI GdOeTbjj, HOQ GdOjf CHh YHO Gddg,J (B743 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd eMeO Hf CMeO Hf HUMGf SCdfi HYV GdbQGA ef Phi GdELJgGO hGdPcGA Cf GNJUQ dg HGH hba MeRI hCHjf CbSGeg hQSeg hgeRg aCLHJg s
(3BNQgG (B:s
(3aUd gTGe jba Ydi LejY CbSGe GdgeR EPG cGf eJWQakG ceG jba Ydjg MeRg ai LejY eG JbOe ef GdHOd hGdfbd hGdEOZGe hGdJSgjd JeJ CbSGe CMcGe GdHGH HJSgjd GdLdjd GdhgGH s
(3GdfSNI HgG MhGTs
(3HChdgG hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQNI SfI (B1373(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B150s
Keywords: (3GdbQGAGJ hGdJLhjOs